1972
DOI: 10.1530/jrf.0.0280041
|View full text |Cite
|
Sign up to set email alerts
|

The Permeability of Bull Spermatozoa to Water, Polyhydric Alcohols and Univalent Anions and the Effects of the Anions Upon the Kinetic Activity of Spermatozoa and Sperm Models

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 25 publications
(38 reference statements)
1
10
0
2
Order By: Relevance
“…The bovine spermatozoa have the ability to swell in a hypo osmotic medium (Drevius and Eriksson, 1966;Bredderman and Foote, 1969;Drevius, 1972). The study conducted by Salah et al, confirmed the ability with an average swelling close to that reported for human spermatozoa using the same hypo osmotic solution (Jeyendran et al, 1984).…”
Section: Effect Of Thi On % Live Sperm Of Semensupporting
confidence: 72%
“…The bovine spermatozoa have the ability to swell in a hypo osmotic medium (Drevius and Eriksson, 1966;Bredderman and Foote, 1969;Drevius, 1972). The study conducted by Salah et al, confirmed the ability with an average swelling close to that reported for human spermatozoa using the same hypo osmotic solution (Jeyendran et al, 1984).…”
Section: Effect Of Thi On % Live Sperm Of Semensupporting
confidence: 72%
“…Possible Modification Drevius (1972c) found that bovine sperm were more permeable to anions than cations and suggested that sperm membrane pores may be positively charged. The incorporation of sperm membrane protein into artificial lipid bilayers has revealed the existence of many channels: nonselective cation channels in mature (epididymal and ejaculated) porcine spermatozoa (Cox et al, 1991) and K ϩ -selective (TEA-sensitive), Na ϩ -selective, divalent cation-and anion-permeable channels in rat epididymal and human ejaculated spermatozoa (Chan et al, 1997;Shi and Ma, 1998;Ma and Shi, 1999).…”
Section: Anion and Cation Channels And Theirmentioning
confidence: 99%
“…The permeability of spermatozoa to a variety of low molecular weight soluble compounds was first examined by Drevius (1971Drevius ( , 1972, in which spermolysis and spermatocrit measurements were taken as indices of the swelling of bovine epididymal spermatozoa. These studies were done at the osmolality of epididymal fluid (c. 353 mmol/kg) where swelling reflects the permeability of the unstressed membrane of the non-swollen cell to the compounds added at high concentration that enter the cell drawing water with them.…”
Section: Permeability Of Spermatozoamentioning
confidence: 99%